Stress and Diabetes Mellitus: Pathogenetic Mechanisms and Clinical Outcome - Ingrosso, Diletta Maria Francesca; Primavera, Marina; Samvelyan, Sona; Tagi, Veronica Maria; Chiarelli, Francesco (Hormone research in paediatrics, 2023)
Evidence suggests that psychological and physical stress are relevant triggering factors for the onset of type 1 diabetes (T1D) and type 2 diabetes (T2D). The underlying mechanisms involve a complex neuroendocrine structure, involving the central nervous system and the periphery. Psychological stress leads to an increase of serum glucocorticoid concentrations and catecholamines release increasing the insulin need and the insulin resistance. According to the β-cell stress hypothesis, also causes of increased insulin demand, such as rapid growth, overweight, puberty, low physical activity, trauma, infections, and glucose overload, are potentially relevant factors in development of T1D. It has also been demonstrated that chronic stress and obesity form a vicious circle which leads to a definitive metabolic failure, increasing the risk of developing T2D. In this review, we will provide the most recent data concerning the role of stress in the outcomes of T1D and T2D, with a focus on the role of physical and psychological stress on the onset of T1D.